The Effect Of Different Stocking With Vitamin C Supplementation Feed On The Growth And Survival Of Tilapia (Oreochromis niloticus) - ayu, dewa; Restu, I Wayan; Susylowati, Dewi; Tangguda, Sartika (Journal Of Artha Biological Engineering, 2025)
Tilapia (Oreochromis niloticus) is one of the freshwater fish commodities with significant economic value. The stocking density of a cultivation container is one of the principles that need to be understood, since the denser the stocking in a container, the more competition for feed and oxygen there will be, which can negatively impact fish health. Determining the right stocking density and vitamin C supplementation can be a solution for farmers in maintaining fish health to increase productivity. The purpose of this research was to determine the best stocking density through vitamin C supplementation as seen from the growth data and survival of tilapia during 30 days of maintenance. The research method that will be used is experimental with a Completely Randomized Design. The research consisted of a stocking density treatment of 15 fish/container, a stocking density treatment of 25 fish/container, and a stocking density treatment of 35 fish/container. Each treatment will be given 3 repetitions. Vitamin C supplementation is given in the feed with a dose of 150 mg/kg of feed. The cultivation container used has a volume of 15 L of water as a cultivation medium. Growth and survival data will be analyzed using SPSS and water quality data as supporting data will be analyzed using Ms. Excel and presented descriptively quantitatively. The results of the research showed that the highest length, weight, and survival values were in treatment A (15 fish/L) with a length growth of 2.43 cm and a weight of 2.42 grams and a survival rate of 86.63%. The results of the ANOVA analysis showed that the stocking density treatment had a significant effect on the length of tilapia, but did not have a significant effect on the weight and survival of the fish. The water quality conditions were still at the optimal standard quality values for tilapia maintenance in all treatments.